Assessment of HER2 Expression in Canine Urothelial Carcinoma of the Urinary Bladder. Issue 3 (May 2019) - Tsuboi, Masaya; Sakai, Kosei; Maeda, Shingo; Chambers, James K.; Yonezawa, Tomohiro; Matsuki, Naoaki; Uchida, Kazuyuki; Nakayama, Hiroyuki
Canine urothelial carcinoma (UC) has a poor prognosis and high metastatic rate. Human epidermal growth factor receptor 2 (HER2), a receptor tyrosine kinase involved in cell proliferation and differentiation regulation, has been attracting interest as a therapeutic target molecule for human breast cancer. This study investigated expression of the canine homolog of HER2 (ERBB2) in canine UC, and its association with clinical factors. Since it has been controversial whether commercial anti-human HER2 antibody (Dako A0485) correctly recognizes the canine homolog of HER2, an application of the antibody using a canine UC cell line was validated first. By Western blot, a single band at the appropriate size for canine HER2 (185 kDa) was recognized. Immunohistochemistry for HER2 was performed on 23 samples of UC, 8 samples of polypoid cystitis, and 8 samples of normal urinary bladder, and the results were scored as either 0, 1+, 2+, or 3+ with reference to the evaluation method for human UC. Intense membranous HER2 immunoreactivity was frequently observed in neoplastic cells, especially in grade 2 UC. Minor HER2 expression was found in the epithelial cells of polypoid cystitis and normal bladder. The incidence of HER2 positivity (scores of 2+ or 3+) was 14 of 23 (60.9%) in UC, 3 of 8 (37.5%) in polypoid cystitis, and 0 of 8 (0%) in normal bladder. There was no significant correlation between HER2 positivity and clinical factors. While increased HER2 expression was observed in a subset of urothelial carcinomas, further mechanistic studies are needed to determine its role in the pathogenesis and targeted therapy of this cancer.